2014
DOI: 10.1021/jf504674z
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Morphology, and Assembly Behavior of Kafirin

Abstract: Prolamins from grains have attracted intensive attention in recent years due to their potential in satisfying the demand for environmentally friendly (biodegradable), abundantly available (sustainable), and cost-effective biomaterials. However, for kafirin, the prolamin from sorghum, its composition, structure, morphology, and self-assembly behaviors have not been fully characterized. In this paper, kafirin was extracted from the whole sorghum grain and found to contain 68, 14, 6, and 12% of α-, β-, and γ-frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 45 publications
(66 reference statements)
6
51
0
Order By: Relevance
“…All the prolamin preparations exhibited higher and more distinct αhelical peaks ( Figure 5C). This is in agreement with the findings of Xiao et al (2014), who found that the α-helical content of kafirin increased in solution and was dependant on solvent polarity. As the solvent polarity decreased the amount of α-helical structure increased.…”
Section: Secondary Structure and Stability Of Zein And Kafirin Preparsupporting
confidence: 93%
“…All the prolamin preparations exhibited higher and more distinct αhelical peaks ( Figure 5C). This is in agreement with the findings of Xiao et al (2014), who found that the α-helical content of kafirin increased in solution and was dependant on solvent polarity. As the solvent polarity decreased the amount of α-helical structure increased.…”
Section: Secondary Structure and Stability Of Zein And Kafirin Preparsupporting
confidence: 93%
“…Kafirin protein with a purity of 90% was extracted from whole sorghum grain in our lab and its properties were reported in our previous work (Xiao et al, 2015). Na-form carboxymethyl-chitosan was purchased from Nantongxingcheng Biological Product Inc. (Nantong, Jiangsu Province, China), with a deacetylation degree of 99%.…”
Section: Methodsmentioning
confidence: 99%
“…Kafirin was extracted from sorghum by using ultrasound-assisted tert-butanol extraction method (Xiao et al, 2015a). Briefly, sorghum flour was defatted with n-hexane and washed with water and 0.5 mol L À1 NaCl to remove albumin and globulin proteins, respectively.…”
Section: Kafirin Preparationmentioning
confidence: 99%